Mundus Vult Decipi: RuPaul’s Drag Race as Part of the Culture Industry - Verhagen, Eelke André (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
In this article I examine the ways in which the competitive reality television franchise RuPaul’s Drag Race (RPDR), immensely popular with Western LGBTQ+-communities, can be considered a product of what Theodor W. Adorno and Max Horkheimer identified as the Culture Industry (CI). On the one hand, this allows for a concrete application of the CI-thesis and the exploration of possible lines of critique concerning RPDR and its effects on its viewership, while, on the other hand, it is an opportunity to evaluate the aptitude of the CI-thesis for critical analysis in the 21st century. While the concepts related to the CI-thesis turn out to be remarkably productive, its latent totalitarian and pessimistic framework tends to skew any analysis. This may warrant supplementing its coarse-grained perspective with a more fine-grained empirical investigation